1991
DOI: 10.1097/00000658-199111000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Blood Contamination and Injury to Operating Room Personnel

Abstract: The potential for transmission of deadly viral diseases to health care workers exists when contaminated blood is inoculated through injury or when blood comes in contact with nonintact skin. Operating room personnel are at particularly high risk for injury and blood contamination, but data on the specifics of which personnel are at greater risk and which practices change risk in this environment are almost nonexistent. To define these risk factors, experienced operating room nurses were employed solely to obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(66 citation statements)
references
References 10 publications
3
62
0
1
Order By: Relevance
“…This is similar to results reported by Jagger et al 8 that showed that residents and attending physicians accounted for 36% and 28% of exposures, respectively, and a French study that observed approximately 35% of BBF exposures occurred among surgeons. 16 Consistent with our results, previous studies have shown procedure duration and estimated blood loss to be risk factors [13][14][15]18 ; at least 1 prior study found an association with number of personnel in the surgical field. 15 Also, another prior study has demonstrated differences in BBF exposures rates across surgical services.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This is similar to results reported by Jagger et al 8 that showed that residents and attending physicians accounted for 36% and 28% of exposures, respectively, and a French study that observed approximately 35% of BBF exposures occurred among surgeons. 16 Consistent with our results, previous studies have shown procedure duration and estimated blood loss to be risk factors [13][14][15]18 ; at least 1 prior study found an association with number of personnel in the surgical field. 15 Also, another prior study has demonstrated differences in BBF exposures rates across surgical services.…”
Section: Resultssupporting
confidence: 91%
“…16 Consistent with our results, previous studies have shown procedure duration and estimated blood loss to be risk factors [13][14][15]18 ; at least 1 prior study found an association with number of personnel in the surgical field. 15 Also, another prior study has demonstrated differences in BBF exposures rates across surgical services. 32 Although the lack of association between shift and BBF exposures may be surprising, this finding is consistent with 1 study that examined all BBF exposures at a university hospital and found no association with time of day.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…10,11 Surgeons and surgical residents are usually at higher risk for PIs than other operating room personnel. [12][13][14][15][16] Makary and colleagues 17 found that by their final year of training, 99% of surgical residents had had a needle-stick injury. Despite high PI rates, PI underreporting among surgeons remains the highest among hospital workers.…”
mentioning
confidence: 99%
“…Appropriate protective draping and garments made of non-woven impervious materials are required to provide an effective barrier between the patient and the surgical team. The likelihood of body contamination increases as the blood loss or surgical time increases [20][21][22][23]. Techniques to reduce surgical time for example using bone graft substitutes instead of autologous iliac crest grafting is a consideration [24].…”
Section: Review Articlementioning
confidence: 99%